Impact of decreased lymphocyte, total cholesterol, and albumin levels at discharge on all-cause death in patients with acute heart failure. (14th October 2021) - Kato, T; Yaku, H; Yamamoto, E; Inuzuka, Y; Tamaki, Y; Ozasa, N; Kimura, T
Abstract: Background: Lymphocyte, total cholesterol, and albumin levels consist of Controlling Nutritional Status (CONUT) score, which has been reported to prognosticate patients with acute heart failure (AHF). However, the influence of each component of CONUT score on outcomes in patients with AHF was not fully elucidated. Purpose: We aimed to evaluate the prognostic implication of the decrease in lymphocyte, total cholesterol, and albumin levels in patients with AHF. Methods: We analyzed 1812 AHF patients in whom data at discharge were available from a multicenter registry. The decrease of lymphocyte (Ly) count was assigned with Ly≥1600/mL (31.0%), 1200≤ Ly <1600 (26.9%), 800≤ Ly <1200 (28.6%), Ly <800 (13.5% of patients). The decrease of total cholesterol (TC) was assigned with TC≥180mg/dL (28.9%), 140≤ TC <180 (42.2%), 100≤ TC <140 (26.7%), TC <100 (2.1% of patients). The decrease of albumin (Alb) was assigned and doubled with Alb≥3.5g/dL (45.7%), 3≤ Alb <3.5 (35.1%), 2.5≤ Alb <3 (15.2%), Alb <2.5 (3.9% of patients). The primary outcome measure was all-cause death after discharge from the index hospitalization. Cumulative incidences were estimated by the Kaplan-Meier method and differences were assessed with the log-rank test. We constructed multivariable Cox proportional hazard models to estimate the risk of the decrease in each value per grade, with the results expressed as the hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Cumulative one-year incidence of the all-cause death was higher with decreasing Ly, TC, and Alb levels (P<0.0001, P<0.0001, and P=0.02, respectively) (Figure 1). The adjusted hazard ratio for all-case death per grade decrease is most prominent in albumin (HR: 1.36, 95% CI: 1.20–1.54), followed by lymphocyte count (HR: 1, 23, 95% CI: 1.10–1.38), whereas it became insignificant in total cholesterol (HR: 1.05, 95% CI: 0.91–1.21). Conclusions: The prognostic implications after discharge were different in albumin, lymphocyte count, and total cholesterol in patients with AHF. Funding Acknowledgement: Type of funding sources: None.